Exploring Teachers’ Perception of Online Engagement in Higher Education in New Zealand - Mani, Krishan (Pacific Journal of Technology Enhanced Learning, 2021)
Student retention in higher education online learning is important for most education institutes around the world. Understanding what contributes to good learning engagement and key factors affecting engagement is important in improving online engagement. Online learning engagement is a very broad topic with multidimensional and interrelated factors that affect how engagement evolves. This study investigated higher education teachers’ perceptions of what online engagement means. It examined the importance of teachers' perceptions of online engagement in higher education with a focus on how teachers’ perceptions of engagement compare and the importance they placed on factors that help them identify the different forms of engagement.  The study also explored whether the teachers’ perspectives were similar in terms of what equates to good learner engagement and what good engagement results into. An extended literature review was carried out to inform the research. As the study eventually aims to gather responses about engagement from both learners and teachers, the methodology for the project was Case Study.  Yin (1989, p.13)) explains that this approach is consistent when “the focus is on a contemporary phenomenon within some real-life context”.  A survey using Microsoft 365 forms was conducted among higher education teachers with online teaching experience in various education disciplines in New Zealand. The Findings from this initial step showed first, there are various definitions, and each teacher had a slightly different perspective of what engagement involved. The study also highlighted the similarities and gaps in terms of online engagement from a teacher’s point of view.